Analisis Tingkat Kesesuaian Syariah Dalam Proses Produksi Pewangi â€œFreshâ€ Laundry Pada Roicool Cipta Mandiri - Faina, Lina (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to determine the extent to which the conformity level of laundry fragrance products, what factors can affect the level of conformity of sharia in the laundry fragrance production process, as well as how the implementation of business licenses for laundry fragrance product home industries is enforced. This research is a field research with a qualitative approach using a qualitative paradigm of social construction phenomenology. The data collection techniques are carried out by observation, interviews, and documentation. While the object of this research is the owner of a home business or home industry "fresh" laundry fragrance. The results of this study indicate the level of conformity of sharia in the laundry fragrance production process is that the raw materials used in fragrances include perfume seeds, methanol, coolers, and preservatives which are halal, safe and harmless materials and on the safety of the production process and the safety of the production environment ensured safe and protected from dangerous objects. The factors for the production of laundry fragrances are the raw materials obtained from chemical materials that have been tested and confirmed to be safe for use in the production of laundry fragrances, the natural resources that are processed into raw materials for fragrances are perfume seeds derived from plant extracts such as roses, jasmine, lavender, and others, human resources are experiencing problems because man power or labor to process laundry fragrance products is only done by the owner himself without any interference from other people, then the capital used is still relatively limited, as well as technology (machines ) that is used is still classified as manual because it still uses simple tools. Then, the application for a home industry permit for the production of laundry fragrances has not yet been carried out because to do this requires a lot of costs and a lot of time.